2019
DOI: 10.1186/s12870-019-1809-8
|View full text |Cite
|
Sign up to set email alerts
|

Iso-Seq analysis of the Taxus cuspidata transcriptome reveals the complexity of Taxol biosynthesis

Abstract: Background Taxus cuspidata is well known worldwide for its ability to produce Taxol, one of the top-selling natural anticancer drugs. However, current Taxol production cannot match the increasing needs of the market, and novel strategies should be considered to increase the supply of Taxol. Since the biosynthetic mechanism of Taxol remains largely unknown, elucidating this pathway in detail will be very helpful in exploring alternative methods for Taxol production. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 75 publications
(109 reference statements)
6
46
0
Order By: Relevance
“…The average length of consensus sequences ranged from 925 bp to 1,438 kb (Figure S1). The number of consensus transcripts significantly exceeded the expected number of expressed genes, however, this is consistent with other reference genome-free IsoSeq analyses (Li et al, 2017; Kuang et al, 2019; Yan et al, 2019). Inflated numbers of consensus transcripts can result from sequencing of multiple alternatively spliced isoforms of the same gene, sequencing of incompletely processed mRNA molecules (Martin et al, 2014), high sequence error rates preventing multiple sequences from the same transcript being collapsed into a consensus, divergent haplotypes of the same locus present in our clonally propagated, wild collected, or partially inbred starting material, or contamination of the original samples with mRNA from non-target organisms.…”
Section: Resultssupporting
confidence: 89%
“…The average length of consensus sequences ranged from 925 bp to 1,438 kb (Figure S1). The number of consensus transcripts significantly exceeded the expected number of expressed genes, however, this is consistent with other reference genome-free IsoSeq analyses (Li et al, 2017; Kuang et al, 2019; Yan et al, 2019). Inflated numbers of consensus transcripts can result from sequencing of multiple alternatively spliced isoforms of the same gene, sequencing of incompletely processed mRNA molecules (Martin et al, 2014), high sequence error rates preventing multiple sequences from the same transcript being collapsed into a consensus, divergent haplotypes of the same locus present in our clonally propagated, wild collected, or partially inbred starting material, or contamination of the original samples with mRNA from non-target organisms.…”
Section: Resultssupporting
confidence: 89%
“…The GO annotation analyses showed that “metabolic process”, “cellular process”, “binding”, “catalytic activity”, “cell”, and “cell part” comprise the majority of subcategories, indicating that the organs of P. chienii experience active cell metabolism to accumulate sufficient nutrition for the future growth and development of the organs. These GO terms are consistent with the previously investigated Taxus cuspidata transcriptome [ 25 ] and the Taxus mairei transcriptome [ 40 ]. The KEGG annotation analysis showed that “carbohydrate metabolism” and “signal transduction” are the top two pathways with the most abundant unigenes.…”
Section: Discussionsupporting
confidence: 91%
“…TFs regulate gene expression via interactions with themselves and other proteins under plant stress response [ 43 ]. In our study, we identified 1678, 2432, 1706, and 2497 TFs for the root, stem, leaf, and strobilus, respectively, belonging to 66 different families, which were comparable to those of another conifer species T. cuspidata (1940 TFs), and the model organism A. thaliana (2357 TFs) [ 25 ]. C2H2, C3H, bHLH, and bZIP were the most represented TF families in all four organs of P. chienii .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While H. amplexicaulis exhibited the shortest consensus transcript length, this was not reflected in a reduced number of complete ORFs-those containing both an in-frame ATG and stop codon and occupying at least 60% of the total transcript length. The number of consensus transcripts significantly exceeded the expected number of expressed genes; however, this is consistent with other reference genome-freeIsoSeq analyses(Kuang, Sun, Wei, Li, & Sun, 2019;Li et al, 2017;Yan et al, 2019). Inflated numbers of consensus transcripts can result from sequencing of multiple alternatively spliced isoforms of the same gene, sequencing of incompletely processed mRNA molecules(Martin et al, 2014), high sequence error rates preventing multiple sequences from the same transcript being collapsed into a consensus, divergent haplotypes of the same locus present in our clonally propagated, wild collected, or partially inbred starting material, or contamination of the original samples with mRNA from non-target organisms.…”
supporting
confidence: 89%